PEMBERDAYAAN MAHASISWA MELALUI PROGRAM KONSELING KESEJAHTERAAN DIGITAL UNTUK MENEKAN DAMPAK NEGATIF SCROLL CULTURE - Weni Kurnia Rahmawati; Mudafiatun Isriyah; Duwi Sitoresmi (STKIP PGRI SITUBONDO, 2025)
The development of digital technology has brought ease of access to information and communication, but on the other hand, it has also given rise to the phenomenon of scroll culture, a habit of excessively browsing social media without a clear purpose. This behavior can reduce focus on learning, increase social anxiety, and impair students' psychological well-being. This community service activity aims to empower students through a digital well-being counseling program focused on strengthening self-awareness and emotional regulation in digital media use. The implementation method included an initial digital behavior assessment, a digital well-being counseling workshop, and individual and group mentoring using emotional regulation theory. This program was conducted over three months, involving students from various study programs. The materials provided included: (1) understanding the concept of digital well-being, (2) strategies for managing emotions in digital activities, and (3) applying mindful scrolling techniques to control the duration and quality of social media interactions. The results of the activity showed increased student awareness of the importance of digital balance and a decrease in the frequency of unproductive scrolling. Furthermore, students demonstrated improved abilities in recognizing emotions, managing online time, and using social media for self-development. This activity is expected to serve as a model of good practice for higher education institutions in developing counseling services that are adaptive to digital challenges and oriented towards student mental well-being.